The influence of mixing on lysozyme renaturation during refolding in an oscillatory flow and a stirred-tank reactor - Lee, Chew Tin; Buswell, A. Mark; Middleberg, P. J. (2002)
Protein refolding is a key unit operation in many processes that produce recombinant biopharmaceuticals using Escherichia coli. Yield in this step generally controls overall process yield, and at industrially relevant protein concentrations is limited by aggregation. While most refolding operations are optimised with respect to chemical environment, the physical processes affecting yield have been neglected. In this study, we demonstrate that refoldingyield for the model protein lysozyme is dependent on mixing intensity during dilution refolding. This is shown for two different reactor configurations: a standard stirred-tank reactor and a novel oscillatory flow reactor. We further show that the effect of mixing is dependent on the type of chaotrope employed for denaturation. Yield falls significantly when mixing intensity is decreased following urea denaturation, while the effect of mixing is not apparent when guanidine hydrochloride is employed as the denaturant. In batch tests we further confirm that, for urea, the "path" of dilution affects yield, and hence the observed sensitivity to mixing is not unexpected. We conclude that mixing is a critical parameter that must be optimised in industrial reactors, along with the usual chemical and protein-specific parameters.